Women's willingness for cervical cancer screening and associated factors among women attending health services in Addis Ababa, Ethiopia - Tangute Demas; Teshale Biku; Tewodros Getinet; Bereket Fantahun; Delayehu Bekele; Negat Woldehawariat; Rahel Muzemir; Martha Shoarega (SAGE Publishing, 2024)
Background: Cervical cancer is one of the most common causes of cancer-related morbidity and mortality globally. In developed countries, effective screening programs reduced its burden. However, in Ethiopia, cervical cancer remains a major public health problem despite the screening service being available free of charge. Objective: The aim of this study was to assess women's willingness for cervical cancer screening services and associated factors among women attending health services in Addis Ababa, Ethiopia. Design: An institutional-based, analytic, cross-sectional study was conducted among sexually active women attending health facilities from August to September 2022. Methods: A pretested interviewer-administered questionnaire was used for data collection. Data were analyzed using SPSS version 25. Logistic regression was used to determine different variables' frequencies and associated factors. A p value of <0.05 was considered statistically significant. Result: Four hundred twenty-two women were approached, and 394 (93.4%) met the study inclusion criteria. Study participants had a minimum of 1 and a maximum of 6 sexual partners in their lives. A total of 256 (64.9%) study participants had heard about cervical cancer. Among those who heard about cervical cancer, only 22 (8.6%) had been tested for cervical cancer. Of those who did not receive cervical cancer screening, only 175 (47.0%) are willing to receive cervical cancer screening. Age, religion, marital status, place of residence, educational level, occupation, and hearing about cervical cancer were found to be statistically significant. Women who heard about cervical cancer were 15.2 times more likely to take the test compared to those who never heard about cervical cancer before the study. Conclusion: Women's willingness to be screened for cervical cancer is low despite many of the study participants having more than one partner in their lives and being at risk for cervical cancer. Only a few participants had been screened for cervical cancer. Women who had heard about cervical cancer were more likely to take the screening service compared to those who had never heard it before. This highlights the need to prioritize raising awareness about the benefits of cervical cancer screening services.